Characterization of \(ε\)-nearest points in spaces with asymmetric seminorm - Costică Mustăţa (Journal of Numerical Analysis and Approximation Theory, 2004)
In this note we are concerned with the characterization of the elements of \(ε\)-best approximation (\(ε\)-nearest points) in a subspace \(Y\) of space \(X\) with asymmetric seminorm. For this we use functionals in the asymmetric dual \(X^{b}\) defined and studied in some recent papers [1], [2], [5].